Studies of the early stages of the dynamic setting process of chemically activated restorative glass-ionomer cements - Fernanda M. Tsuzuki; Renata C. Pascotto; Luis C. Malacarne; Antonio C. Bento; Antonio Medina Neto; Lidiane Vizioli de Castro-Hoshino; Monique Souza; John W. Nicholson; Mauro L. Baesso (Medical Journals Sweden, 2021)
Objective To evaluate the early stages of the setting process of chemically activated restorative glass-ionomer cements (GICs). Material and methods Five GICs were evaluated (n = 5): Equia Forte (GC), Equia Forte HT (GC), Ketac Universal (3M ESPE), Maxxion R (FGM) and Riva Self Cure (SDI) by Thermography, Fourier Transform Infrared Attenuated Total Reflectance Spectroscopy (FTIR-ATR) and Gillmore needle indentation mechanical testing. The FTIR-ATR spectra showed the formation of metal carboxylates within the cements and enabled the stabilization time (ST) to be determined and the thermographic camera measured the temperature field images in the sample. Data were statistically analyzed by ANOVA and Tukey-Kramer (α = 5%). Results The Gillmore needle test showed that the order of hardening was opposite to the order of ST values determined by FTIR. The results with the thermographic camera showed two stages of temperature variation, which coincided with the evolution of specific infrared bands. The exception was Maxxion R, which showed only a single step change in temperature. Conclusion The early stages of the GIC setting reaction show temperature changes, both endothermic and exothermic, at specific times, confirming the occurrence of individual chemical reactions. The early setting involves reactions other than carboxylate formation. Significance: This study gives further detail of the early stages of the setting of GICs, and past research regarding the setting reaction of GIC.